Pengaruh Logam Berat Pb Limbah Aktifitas Penambangan Timah Terhadap Kualitas Air Laut di Wilayah Penangkapan Cumi-Cumi Kabupaten Bangka Selatan - Arif Febrianto (Akuatik: Jurnal Sumberdaya Perairan, 2014)
The main potential that can be used in coastal and marine areas including fisheries, coastal aquaculture, tourism and mining of South Bangka. Region of tin mining activities in the South Bangka coastal region is also a fishing ground for fishermen to conduct fishing activities. Water quality parameters include temperature, brightness, salinity, dissolve oxygen, water flow, depth, heavy metal content of seawater and plankton. Wastes from mining activities are dumped directly in the coastal regions generally in the form of waste containing heavy metals Pb. The purpose of this study was to determine the effect of Pb waste of tin mining activities on water quality in the sea fishing area (fishing ground) squid in South Bangka regency. The method used in this research is descriptive method, which aims to make a description or picture of systematic, factual and accurate effect of Pb on sea water. Pb heavy metal content in the water was analyzed based on SNI methods by using AAS refers to the sea water quality standards for heavy marine life KepMenLH 2004 (mg / l). The results of observation can average content of Pb in the region are mining of 0.113 mg / l, while in the area which is no mining of 0,0411mg / l. So H1 received, there is the influence of mining activities on the Pb content of sea water in the area of catching squid.